Comparative study to use nanofluid ZnO and CuO with phase change material in photovoltaic thermal system. (18th February 2019) - Manigandan, Sekar; Kumar, Vasanth
Summary: In this study, the simultaneous use of nanofluid and phase changing material as a coolant for photovoltaic fluid collector system and its effects are investigated experimentally. Two types of nanofluid are taken for the consideration, that is, ZnO and CuO, which are water‐based fluid. The experiments are performed in five different types of photovoltaic thermal system conventional: PT, PVT (ZnO), PVT (CuO), PCM medium (PVT/PCM/ZnO), and PCM medium (PVT/PCM/CuO). The results are obtained for surface temperature, energy, and thermal efficiency, and it is compared with each other. Further, the effect of the nanofluid as the effective alternative for pure deionized water is measured. From the results, it is evident that the PVT/PCM/CuO system minted 15% high electric output compared with convention module. Furthermore, the addition of the CuO nanofluid increases the thermal output significantly up to 8% for PVT and 12% for PCM without energy consumption. It also found that the nanofluid increases the overall energy efficiency of the system compared with convention PV. Abstract : The use of nanofluid ZnO and CuO with PCM was proposed. It is identified that the nanofluid not only enhances the power output but also contributes to reducing the surface temperature to appreciable levels. Furthermore, PCM medium with nanofluid can be an appropriate selection to improve the cooling in the PVT system without any extra energy consumption. Highlights Simplified PVT‐PCM system has been developed with nanofluids. Novel method has been proposed to incorporate the ZnO and CuO on PCM/PVT. The nanofluid (ZnO and CuO) in PCM reduces the surface temperature by 43% and 47%. Incorporation of PCM and nanofluid improved the electrical efficiency by 16% and electrical output by 15%. The cumulative thermal output for PCM is increased by 46% compared with the PV module. Nanofluid CuO shows a profound effect comparing to ZnO